As representações sociais dos graduandos do último período de enfermagem acerca do doente e da doença mental - Silva, Júlia Carolina de Mattos Cerioni (2015)
Introduction: The required skills and attitudes for actions on mental health in nursing students are influenced by pre-stigmatized concepts brought by social and family experience. With the advent of the Psychiatric Reform, which among others resulted in the de-institutionalization, people with mental disorders have been treated in open places, i.e., Psychosocial Care Center - PCC, Therapeutic Residences - TR, Mental Health Clinics, etc.; and attend public areas to health care (Basic Health Units, Emergency Rooms and others). The nursing contact with people with mental disorders shall happen in a multifaceted reality, requiring that these professionals are prepared and willing to meet this demand. The Social Representations of students regarding this specific public are extremely important, so that after have been identified, are considered in the vocational nursing able to such assistance. Objectives: Identifying the social representations on the sick patient and the mental illness of the nursing senior students and describe the factors related to representations regarding the knowledge, perception and behavior. Methods: It was a descriptive and exploratory research, with qualitative-quantitative approach, highlighting the Theory of Social Representations as the theoretical reference and the Collective Subject Discourse (CSD) as the methodological framework, with the analysis in the thematic. Eleven nursing graduating students from a Private Education Institution in São Paulo State participated on the study. A verbally answered interview, with three guiding questions, was used to collect data about knowledge, perception and attitude towards the sick patient and the mental illness. Results: Most of the participants are female, with mean age of 25 years, not working in the health area. The Social Representations associated with the knowledge presented the relationship with biomedical characterization in 75% (manifestation, classification, etiology, etc.), influenced by Flexnerian matrix of health education; to the axis perception, 30.23% related the need for intervention (Treatment, Care, etc.) linked to the historical process of "acting" in nursing; and 20.93% said they had changed their perception after the main working stage, associated with practices local characteristics called Psychosocial Care Center (PCC II). About the behavior, 63.33% expressed a consistent attitude with the precepts of the Psychiatric Reform (Integrating the Society, Watch Team, Humanized Approach, etc.), influenced by the content covered in class, and again in the working stage site. Conclusion: - It was concluded that for the knowledge, perception and behavior matching against the diseases and the mentally ill, it needs proper content to new ways of mental health care, consistent location with the new practice recommended by the Ministry of Health and a teaching model that adds completeness to the necessary and inherent to the profession content, enabling the experience of relationships and reflective attitude